Pengujian Potensi Diuretik Infusa Daun Bangun-Bangun (Plectranthus Amboinicus (Lour.) Spreng) Yang Diujikan Pada Tikus Jantan (Rattus Norvegicus Berkenhout) Galur Wistar - Monica Suryani; Jon Kenedy Marpaung; Suharyanisa Suharyanisa; Mestika Lumbantoruan (Lembaga Pengembangan Kinerja Dosen, 2023)
Diuretics act on the kidneys to increase the excretion of water and sodium chloride. The working principle of diuretics in general is to reduce electrolyte reabsorption by the renal tubules, where an increase in electrolyte excretion will be accompanied by an increase in water excretion which is needed to achieve osmotic balance. Bangun-Bangun leaf contains polyphenolic compounds, saponins, glycosides, flavonoids, and essential oils. Bangun-Bangun leaves types of flavonoids, namely quercetin, apigenin, luteolin, salvigenin, and genkwanin. Apigenin is known as a compound that functions as a diuretic. IDBB was obtained from the infusion technique with distilled water and then the infusion was used on 25 diuretic rats which were divided into 5 groups. Group I (negative) Na-CMC 0.5%, group II, III, IV, IDBB doses of 10, 20, 40%, and group V (positive) Furosemide 3.6 mg/kgBW were given orally. Rats were given aquadest orally at a dose of 15 ml/kgBW. Mice were placed in metabolic cages, then a physical examination of urine was carried out every 1 hour for 6 hours. The results showed that the IDK with the best dose was 40% which gave an increase in urine volume, had an effect on urine pH, had an effect on urine specific gravity, had an effect on urine color, and had an effect on urine clarity.